Richard Wright's art of tragedy - Joyce, Joyce Ann, 1949- (University of Iowa Press, 1986)
Annotation. First published (hardcover) in 1986. Joyce focuses specially on the stylistic characteristics of Wright's most successful novel to show how his language merges with his subject matter to illuminate Native son as a tragedy. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Wright, Richard, -- 1908-1960. -- Native son.; Native son (Wright, Richard); African American men in literature.; Tragic, The, in literature.; Hommes noirs américains dans la littérature.; Tragique dans la littérature.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM / General; African American men in literature; Tragic, The, in literature; Native son (Wright)